2007
DOI: 10.5334/ijic.186
|View full text |Cite
|
Sign up to set email alerts
|

‘Trying to do a jigsaw without the picture on the box’: understanding the challenges of care integration in the context of single assessment for older people in England

Abstract: Introduction: Demographic ageing is one of the major challenges for governments in developed countries because older people are the main users of health and social care services. More joined-up, partnership approaches supported by information and communications technologies (ICTs) have become key to managing these demands. This article discusses recent developments towards integrated care in the context of one of the arenas in which integration is being attempted, the Single Assessment Process (SAP) to support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…By focusing upon interactions in the workplace, it supports the recognition of the technology's material properties, as well as human agency, as a factor in the enactment of e‐government. The notion of ‘seamless’ care enabled by technology could be seen then as an over‐structuring and over‐integration of policy, practice, and technical resources aimed at creating the solution of the ‘full picture’ (Wilson et al. , 2007; Wilson and Baines, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…By focusing upon interactions in the workplace, it supports the recognition of the technology's material properties, as well as human agency, as a factor in the enactment of e‐government. The notion of ‘seamless’ care enabled by technology could be seen then as an over‐structuring and over‐integration of policy, practice, and technical resources aimed at creating the solution of the ‘full picture’ (Wilson et al. , 2007; Wilson and Baines, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…English studies analysing the normalization of IHTs in usual care have shown that various technologies often fail because they did not acknowledge the ways health deliverers usually get their work done or how they understand the work they are doing [25,36,39,44,47,71,72]. These studies highlighted that in order to become workable, professionals' identities, situated knowledge, local routines, practices, and infrastructures must be acknowledged.…”
Section: Discussionmentioning
confidence: 96%
“…'prototypes' or 'probes' is commonly used in market research and increasingly in social research (Gaver 2004, Jenkings andWilson 2007). Each workshop was designed for a different set of stakeholders involved in directory production.…”
Section: Policy Context: Joined-up Services and Provider Diversitymentioning
confidence: 99%